HUBUNGAN PEMANFAATAN BUKU KESEHATAN IBU DAN ANAK DENGAN TINGKAT KECEMASAN IBU HAMIL PRIMIGRAVIDA DI WILAYAH KERJA PUSKESMAS BATURITI I - Yuliani, Komang Tri; Mahayati , Ni Made Dwi; Tirtawati , Gusti Ayu (Seroja Husada: Jurnal Kesehatan Masyarakat, 2025)
Pregnancy on primigravida can caused anxiety due to a lack of experience and understanding related to the pregnancy process. The provision of Maternal Child Health (MCH) Handbooks was an effort which means to increase the knowledge and understanding of pregnant women in the pregnancy process. This study aimed to determine the relationship between the use of MCH handbooks and anxiety level of primigravida in Working Area of Puskesmas Baturiti I. This study was correlational study with cross sectional approach. A total of 77 pregnant women with primigravida were selected using the purposive sampling technique. The research data was collected through questionnaires and analyzed by the spearman rank test. The results of the study showed the use of MCH handbooks was mostly in good category (58.4%) with anxiety levels mostly in non-anxious category (45.5%). There was a relationship between the use of MCH handbooks and anxiety level of primigravida in Working Area of Puskesmas Baturiti I (p=0.000). The proper and optimal use of MCH handbooks can increase pregnant women's understanding of pregnancy, the delivery process, so that can help pregnant women avoid anxiety. The provision of education with MCH handbooks is expected to be optimized so anxiety level can be minimized.